The Impact of Psychology, Leadership Style, and Sustainable Human Resources on Organizational Performance - Yuddy Giovanna Priscilla; Rafif Shagufta; Dhita Hafizha Asri (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the influence of transformational leadership, employee psychological well-being, and sustainable HR practices on organizational performance, as well as to examine the mediating role of sustainable HR practices in this relationship. Research Methodology: The study used an explanatory quantitative approach with a survey method involving 224 permanent employees at a manufacturing company in Batam City. Data were collected through Google Forms and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS application. Results: The results indicate that transformational leadership, psychological well-being, and sustainable HR practices have a positive and significant effect on organizational performance. Sustainable HR practices also mediate the relationship between transformational leadership and organizational performance, as well as between psychological well-being and organizational performance. Conclusions: The findings indicate that transformational leadership, employee psychological well-being, and sustainable HR practices significantly influence organizational performance, with sustainable HR practices also acting as a mediating variable that strengthens the relationship between leadership and psychological factors toward organizational outcomes, resulting in a comprehensive model explaining their simultaneous effects. Limitations: This study is limited to one manufacturing company in Batam City and uses a cross-sectional design, so it does not capture changes in variables longitudinally. Contributions: Theoretically, this study enriches the literature on sustainable HR practices as a mediating mechanism that links transformational leadership and psychological well-being to organizational performance. Practically, the results of this study provide recommendations for management in designing sustainable work systems to improve organizational competitiveness.